THE EFFECT OF METAL NANOPARTICLES ON FORMALDEHYDE EMISSION FROM WOOD BASED MATERIALS - Pinchevska, Olena; Lopatko, Kostyantyn; Lopatko, Larysa; Oliynyk, Rostislav; Sedliačik, Ján (Acta Facultatis Xylologiae Zvolen, 2023)
Considering the significant production volume of wood composite materials, the search for ecological solutions to reduce formaldehyde emissions during their pressing and further operation is urgent. The effect of nanoparticles of zinc, aluminium, and iron metals on formaldehyde emission from particleboard samples during their manufacture and subsequent exposure for three weeks is examined in the paper. Nanoparticles of metals were produced by the electro-spark method. In order to determine the priority metal, the method of analysis of hierarchies and search experiments was used. Samples of particleboard were made with the addition of a modified glue based on UF resin. Nanoparticles of the metals Zn, Al, and Fe were used in concentrations of 2% and 8%, respectively, to modify the adhesive resin. Measurements of the level of free formaldehyde were carried out on the third and seventeenth days after the pressing of particleboard samples. The results of experimental studies confirmed the theoretical calculation of priority based on the selected assessment criteria. The best results were observed when zinc was used as a filler at a concentration of 8%.